2014
DOI: 10.1371/journal.pone.0100803
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Carryover of Temporal Context Dissociates Response Bias from Perceptual Influence for Duration

Abstract: Recent experimental evidence suggests that the perception of temporal intervals is influenced by the temporal context in which they are presented. A longstanding example is the time-order-error, wherein the perception of two intervals relative to one another is influenced by the order in which they are presented. Here, we test whether the perception of temporal intervals in an absolute judgment task is influenced by the preceding temporal context. Human subjects participated in a temporal bisection task with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
125
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(151 citation statements)
references
References 65 publications
(102 reference statements)
23
125
2
1
Order By: Relevance
“…For example, Wiener and colleagues devised an implicit memory model which assumes that the perception of duration depends on an adaptive memory prior (Wiener and Thompson, 2015;Wiener et al, 2014). That is, the memory prior could be continuously updated by prior duration and could serve as an internal standard for duration judgment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wiener and colleagues devised an implicit memory model which assumes that the perception of duration depends on an adaptive memory prior (Wiener and Thompson, 2015;Wiener et al, 2014). That is, the memory prior could be continuously updated by prior duration and could serve as an internal standard for duration judgment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that duration judgment follows the anchor rule: a short anchor lengthens the perceived duration of subsequent stimuli, whereas a long anchor shortens their perceived duration (Behar and Bevan, 1961;Goldstone et al, 1957;Postman and Miller, 1945). Since the duration aftereffect and the anchor effect present similar outcomes at the behavior level, some researchers suggested that these two phenomena may share the same mechanisms (Heron et al, 2012;Wiener, et al, 2014). However, results of Experiment 2 revealed that although a single anchor duration induced an anchor effect, this had no effect on the CNV amplitude evoked by the test stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also reported that a short anchor stimulus lengthens the perceived duration of subsequent medium duration stimuli, while a long anchor stimulus shortens their perceived duration, which suggested a repulsive duration anchor effect (Postman and Miller, 1945; Goldstone et al, 1957; Behar and Bevan, 1961). Because these two effects result in similar behavioral outcomes on duration perception, some speculated that these two phenomena might share the same mechanisms (Walker et al, 1981; Heron et al, 2012; Wiener et al, 2014). However, there is little direct evidence indicating whether the duration aftereffect is an instance of the duration anchor effect induced by altering the internal reference for duration judgment, or whether the duration anchor effect is an instance of the duration aftereffect induced by a rapid adaptation to duration, or whether they have distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that making decision about time relies not only on the current physical stimuli, but also on an internal reference for time judgment (Grondin, 2005; Dyjas et al, 2012; Bausenhart et al, 2014). For example, the implicit memory model recently suggested that the perception of duration is a noisy sensory process against an adaptive memory prior (Wiener et al, 2014; Wiener and Thompson, 2015). That is, the memory prior is continuously updated by prior durations within a memory window and may serve as an internal reference for duration judgment.…”
Section: Introductionmentioning
confidence: 99%